2013
DOI: 10.1038/pj.2013.12
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a thermosensitive polycation by random copolymerization of N-vinylformamide and N-vinylbutyramide

Abstract: The novel thermoresponsive polycations poly(N-vinylbutyramide-co-vinylamide) (poly(NVBA-co-VAm)), with different mole ratios of poly(VAm) (PVAm):poly(NVBA) (PNVBA), were synthesized as a biomaterial by free radical copolymerization of poly (N-vinylbutyramide-coN -vinylformamide) (poly(NVBA-co-NVF), followed by acid hydrolysis. Such poly(N-vinylamide)s do not generate toxic low-molecular-weight amine compounds by hydrolysis, although the poly(acrylamide) structural isomers do. The mole ratio of PVAm and PNVBA w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Numerous publications clearly indicate the excellent copolymerization abilities of NVF . The copolymerization of NVF with vinyl monomers possessing electron deficient CC double bonds such as acrylates, acrylamides, or maleates yields copolymers with alternating tendencies, while copolymerization with ethylene or vinyl esters forms random types of copolymers .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous publications clearly indicate the excellent copolymerization abilities of NVF . The copolymerization of NVF with vinyl monomers possessing electron deficient CC double bonds such as acrylates, acrylamides, or maleates yields copolymers with alternating tendencies, while copolymerization with ethylene or vinyl esters forms random types of copolymers .…”
Section: Introductionmentioning
confidence: 99%
“…Separately, we reported that water-soluble supra-molecules consisting of urea benzene frameworks (UBDs) having oligoethylene glycol chains (OEGs) showed thermal responsiveness in water solution (Figure ). Upon heating the solution, an abrupt self-assemble behavior with low temperature critical temperature (LCST) took place due to the dehydration surrounding OEGs, forming microsize particles. This LCST property is rare for supra-molecules .…”
Section: Introductionmentioning
confidence: 99%